Synthesis and structural study of the ionic ensemble (RS)-nipecotic acid: oxalic acid: water - Chacon, C. (Tche Quimica Group, 2017)
Multi-component crystals have been studied during recent years from the applications points of view. Particularly are useful in the case of pharmaceutical co-crystals due they play a significant role in the development of new drugs. These materials are considered good alternatives to existing pharmaceutical formulations, as they may help to improve pharmacological properties such assolubility, stability and bioavailability. Single-crystal X-ray diffraction was used to examine the nature of non-covalent interactions in the multi-component crystal (RS)-nipecotic: oxalic acid: water (1:1:1).All three entities are linked by intermolecular interactions. The crystals are orthorhombic, space group Pbca, with a = 11.184(4) Å, b = 11.895(4) Å, c = 16.781(6) Å, V = 2232.4(1) Å3, Z = 8. In this structure, an ionic ensemble assisted by hydrogen bonds, the molecules are connected by O-H.........O and N-H.........O hydrogen bonds, forming linearsemi-oxalate-semi-oxalate chains with intercalated R and S nipecotic molecules. The combination of these intermolecular interactions leads to the formation of a molecular assembly which can be described as a two-dimensional bilayer-like arrangement.